3p/6=-2/3

Simple and best practice solution for 3p/6=-2/3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3p/6=-2/3 equation:



3p/6=-2/3
We move all terms to the left:
3p/6-(-2/3)=0
We get rid of parentheses
3p/6+2/3=0
We calculate fractions
There is no solution for this equation

See similar equations:

| (9x+10)=136 | | 8x-17)=14 | | x+x+9=x | | 8x+17)=141 | | 4x+8x-42=138 | | 6w=25 | | 13,000=1.3x10=1.3×10 | | 3p2-6=1 | | 13,000=1.3x | | 2(x-1)-03x=6 | | -4(4+x)=4 | | -3x+8(x–1)=47 | | 1.5x+2.6=0.8x | | 3 | | 480=(x-8)(480/x+3) | | 12+6b=66 | | 4+6p=-8+32 | | 2x2-19x–126=0 | | 5(-3+7x)=195 | | x–15=80 | | a+6a-5=9 | | X=16.5+-0.5y | | f(2)+f(4)+f(6)=12-3 | | 1-6/f=3 | | 4-7p-3=1-8p | | 3x2​+8=35 | | X/888=y | | X÷888=y | | 4x–22+3x–45=8–2x+26+5x–1 | | 29=z-4 | | -2x-6=−2x−6=3x-213x−21 | | 4(89.950+x=628.35 |

Equations solver categories